Measurements of crosswind influence on a natural draft dry cooling tower for a solar thermal power plant. (15th November 2017) - Li, Xiaoxiao; Gurgenci, Hal; Guan, Zhiqiang; Wang, Xurong; Duniam, Sam
Highlights: A 20 m experimental cooling tower was tested in different crosswind conditions. Air temperature distributions and heat exchanger performances are presented. The mechanism of the crosswind effect on small cooling tower is discussed. Crosswind effect on a small CST power plant is evaluated. Abstract: Crosswind is a significant concern for natural draft dry cooling towers. The concern is more serious for shorter towers. Therefore, the crosswind influence is a significant threat to the use of natural draft dry cooling towers in concentrating solar thermal power plants, which are generally built at sizes smaller than conventional fossil-fired plants and employ relatively shorter towers. While some numerical studies and small lab-scale test reports exist, very few full scale experimental studies have been reported for conventional cooling towers and none for relatively short cooling towers suitable for renewable thermal power plants. To address this gap, a 20-m tall fully instrumented natural draft dry cooling tower was built by the University of Queensland. The tower was designed to serve a future 1-MWe concentrating solar thermal plant on the same site. Its performance was tested under different ambient temperatures and crosswind speeds. The detailed experimental data of the crosswind condition, air temperature distribution inside and outside of the cooling tower and the cooling performance are presented. The experimental data demonstrate the substantial yet complex impact of the crosswind on cooling tower performance. Significant non-uniformities in air and hot water temperature distributions and strong air vortices inside the tower were observed in high crosswind speeds. Unlike tall cooling towers used in large conventional plants, the cooling tower performance does not monotonously decrease with the increase of the crosswind speed. In fact, after the tower performance drops to its lowest level at a wind speed around 5 m/s, the trend is reversed and further increases in the crosswind speed help the tower performance. Analysis shows that this reversal occurs because the tower heat transfer mechanism changes. As crosswind rises above the critical speed, the airflow inside the cooling tower becomes increasingly controlled by the crosswind instead of the natural draft.